Ozone trends derived from the total column and vertical profiles at a northern mid-latitude station - P. J. Nair; S. Godin-Beekmann; J. Kuttippurath; G. Ancellet; F. Goutail; A. Pazmiño; L. Froidevaux; J. M. Zawodny; R. D. Evans; H. J. Wang; J. Anderson; M. Pastel (Atmospheric Chemistry and Physics, 2013)
The trends and variability of ozone are assessed over a northern mid-latitude station, Haute-Provence Observatory (OHP: 43.93° N, 5.71° E), using total column ozone observations from the Dobson and Système d'Analyse par Observation Zénithale spectrometers, and stratospheric ozone profile measurements from light detection and ranging (lidar), ozonesondes, Stratospheric Aerosol and Gas Experiment (SAGE) II, Halogen Occultation Experiment (HALOE) and Aura Microwave Limb Sounder (MLS). A multivariate regression model with quasi-biennial oscillation (QBO), solar flux, aerosol optical thickness, heat flux, North Atlantic Oscillation (NAO) and a piecewise linear trend (PWLT) or equivalent effective stratospheric chlorine (EESC) functions is applied to the ozone anomalies. The maximum variability of ozone in winter/spring is explained by QBO and heat flux in the ranges 15–45 km and 15–24 km, respectively. The NAO shows maximum influence in the lower stratosphere during winter, while the solar flux influence is largest in the lower and middle stratosphere in summer. The total column ozone trends estimated from the PWLT and EESC functions are of −1.47 ± 0.27 and −1.40 ± 0.25 DU yr −1 , respectively, over the period 1984–1996 and about 0.55 ± 0.30 and 0.42 ± 0.08 DU yr −1 , respectively, over the period 1997–2010. The ozone profiles yield similar and significant EESC-based and PWLT trends for 1984–1996, and are about −0.5 and −0.8% yr −1 in the lower and upper stratosphere, respectively. For 1997–2010, the EESC-based and PWLT estimates are of the order of 0.3 and 0.1% yr −1 , respectively, in the 18–28 km range, and at 40–45 km, EESC provides significant ozone trends larger than the insignificant PWLT results. Furthermore, very similar vertical trends for the respective time periods are also deduced from another long-term satellite-based data set (GOZCARDS–Global OZone Chemistry And Related trace gas Data records for the Stratosphere) sampled at northern mid-latitudes. Therefore, this analysis unveils ozone recovery ...